PEMBERIAN PAKAN BUATAN YANG TERINTEGRASI DENGAN LIMBAH RUMPUT LAUT PADA BUDIDAYA IKAN BANDENG (Chanos-chanos) DI KABUPATEN MOROWALI - Sulistiawati, Dwi; Rosyida, Eka; Laapo, Alimuddin (FAPETKAN UNTAD, 2016)
The purpose of this study is (1) determining the dose of waste carrageenan/waste seaweed as an adhesive based on physical and chemical quality of fish feed (2) assessing the effect of artificial feeding containing waste carrageenan on the growth of milkfish. Using experimental design method to determine the dose of waste carrageenan as an adhesive based on physical and chemical quality of fish feed. The treatment consisted of4 doses of test adhesive (addition of 3%, 5%,10% and 15% of waste carrageenan) andeach treatment was applied 3 times repetition. The milk fish feed made from waste carrageenan-shaped pellets that havebeen previously calculated formula of milk fish feed using 4 main raw material, namely corn meal, fish meal, soybean meal andfine bran.Â Determination of the amount/percentage of used materials was calculated using the square method after knowing the standard range of nutrient content of these materials.The results showed that use of waste carrageenan in the milkfish feed can enhance the growth of the higher milkfish.The growth of milkfish is maintained for 3.5 months with the provision of waste carrageenan 3-15% for 3.3 to5.9 g/day.The treatment gives the highest weight gain milkfish (average 5.9 g/day) is the provision of waste carrageenan with a composition of 15% of the total raw material feed.Keywords: Aquaculture milkfish, waste carrageenan, pellet feed.